The urbanization process in the Third World explorations in search of a theory - McGee, T.G (G. Bell and Sons, Ltd., 1971)
A collection of essays whose theme is one of growing disillusionment with the application of urban theories developed in the West to urbanization process in the third world... The first section attempts to show the limitations of the 'similar path' theories and to put forth alternative theoretical models for analysis of urbanization in the third world. The second section is based on the author's fieldwork in Southeast Asia and by actual examples he illustrates the inadequacy of the Western - based theoretical model of the urbanization process.